Visual impact : creative language learning through pictures - Hil, David A. (England : Longman, 1990)
Offers advice on how to use visuals, as well as providing a variety of specific activities based around the idea of using pictures to stimulate language learning in the classroom. The book details ten general techniques for using pictures in specific areas of language teaching.
Includes bibliography.
Keywords: Non-english speaking students